UJI KOMPARASI MODEL KORELASI DALAM MENGANALISIS EFEKTIVITAS PENDAMPINGAN PETANI - Hombing, Yennita Sihombing; Hutahaean, Lintje (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2019)
In Order to apply the agriculture technology or innovation, the farmers requires assistance by researches or extension agent to provide the expected results. The application of agricultural technology or innovation in farmers requires assistance by researchers or extension workers to provide the expected results. This study has an objective to determine the effectiveness among three correlation models, namely: Pearson, Kendall’s tau-b, and Spearman for analyzing the performance of assisting activities. The assessment was done based on the assisting data which collected in North of Bolaang Mongondow District, North Sulawesi Province. As the respondents, the primary data were obtained by questionnaires to 22 of the rice farmers who were randomly selected by PRA. The assisting data focused on the rice production aspect for both of pre-assisting and post-assisting cases. The effectiveness indicator among those correlation models has defined using the number of real analysis variables and the correlation coefficients. According to three models, they produced almost similar coefficient correlation for both of pre-assisting and post-assisting cases. Based on three models, a significant correlation variable which found was a correlation between the age and the experiences. For those significant variable, the differences among those models only appears in the degree of correlation. As a conclusion, the Pearson, Kendall’s tau b, and Spearman correlation models can be used as an alternative methods for analyzing the performance of assisting activities.